(untitled) (Bangladesh Veterinarian, 2024)
Small ruminant production contributes to the livelihood of small-scale farmers. However, the production is low due to several factors, including pneumonic pasteurellosis. The primary causes of infections are Mannheimia haemolytica, Pasteurella multocida, and Biberstinia trehalosi. It is of great importance at the national level. The disease is commonly transmitted through the air causing sporadic and epidemic pneumonia and septicaemia. Clinical signs include respiratory distress with high fever, coughing, difficulty breathing, and thick purulent nasal discharge. They typically occur in individuals with poor immunity. Weak management practices are often linked to stress. The disease incurs significant losses. The existence of many serotypes without cross-protection and the emergence of drug resistance have made its management more challenging. Furthermore, the causal agents are mostly organisms that reside in the upper respiratory tract but might lead to infection in those with reduced immune systems. Hence, it is crucial to prioritise appropriate selection of antimicrobials, reliable diagnosis, and the inclusion of relevant serotypes in developing vaccines to prevent and manage pneumonic pasteurellosis. Bang. vet. 2023. Vol. 40, No. 1 – 2, 25 – 36